INVESTIGATING THE CHALLENGES FACED BY EFL TEACHERS IN DEVELOPING STUDENTS’ 4C SKILLS IN 21ST-CENTURY EDUCATION - Siti Nur Azizah Septiyani; Irsyad Nugraha; Ateng Kurnia (Institut Pendidikan Indonesia Garut, 2023)
This research aims to investigate the challenges faced by EFL teachers in developing students’ 4C skills (Critical thinking, Creativity, Communication, and Collaboration) in 21st-century education., followed by four English teachers in different Junior High School in Garut (two public schools and two private schools). To fulfill this objective, a qualitative case study design with a semi-structured interview as the research instruments was employed. The result revealed that both EFL teachers of public and private schools in junior high school had similar problems in developing students' 4C skills in 21-st century education. Those challenges include the difficulties in understanding certain effective methods of learning that support the development of 4C skills, the obstacles in designing a lesson plan for 4C skills, the insufficiency of facilities and infrastructure, and the challenges in developing students’ confidence and activeness.